Chemoenzymatic Synthesis of Ubiquitous Biological Redox Cofactors - Singh, Priyanka; Guo, Qi; Kohen, Amnon (Synlett, 2017)
Redox cofactors are utilized by a myriad of proteins, ranging from metabolic enzymes to those performing post-translational modifications. Labeled redox cofactors have served as a vital tool for a broad range of studies. This account describes chemoenzymatic syntheses of the isotopically labeled, biologically important redox cofactors: nicotinamide adenine dinucleotide, methylene tetrahydrofolate, and flavin nucleotides. An overview of the general strategy is presented. These examples demonstrate the utility of enzymatic synthesis.1 Introduction2 Nicotinamide Cofactors2.1 Synthesis of Remote-Labeled 14C-NADPH2.1.1 Synthesis of [Ad-14C]NADPH2.1.2 Synthesis of [Carbonyl-14C]NADPH2.2 Synthesis of S- and R-[4-3H]NADPH2.2.1 One-Step S- and Three-Step R-[4-3H]NADPH Synthesis2.2.2 One-Pot, One-Step R-[4-3H]NADPH Synthesis2.3 Synthesis of S- and R-[Ad-14C, 4-2H]NADPH2.3.1 One-Step S-, Three-Step R-[Ad-14C, 4-2H]NADPH Synthesis2.3.2 One-Pot, One-Step R-[Ad-14C, 4-2H]NADPH Synthesis3 Methylene Tetrahydrofolate4 Flavin Nucleotides5 Conclusions and Outlook
Keywords: chemoenzymatic synthesis; isotopic labeling; nicotinamide; flavin; methylene tetrahydrofolate